Optimizing Biomethane Production from Industrial Pig Slurry and Wine Vinasse: A Mathematical Approach - Belén Cañadas; Juana Fernández-Rodríguez; Rosario Solera; Montserrat Pérez (ChemEngineering, 2025)
Pig slurry (PS) and wine vinasse (WV) pose environmental risks if not properly managed. Their composition makes them suitable for anaerobic co-digestion (AcoD), enhancing biomethane production and improving organic matter degradation efficiency. This research applies an innovative Design of Experiments (DoE) approach—specifically the Box–Behnken design (BBD)—to systematically optimize the AcoD process, surpassing traditional single-factor methods by efficiently evaluating the interactions. Variables such as temperature (35 °C, 52.5 °C, 70 °C), substrate ratio (25PS:75WV, 50PS:50WV, 75PS:25WV) and pH (7, 7.5, 8) were tested using a Box–Behnken design which studied the correlations between the experimental data and the model. In fact, the results showed that temperature, ratio, and their interaction significantly influenced biomethane production, being the pH the factor with the least influence on the response. Optimal conditions—pH of 8, temperature of 35 °C and a 50:50 substrate ratio—achieved a biomethane yield of 487.94 CH4/gVS (Volatile Solids). These results demonstrate the effectiveness of the DoE methodology in maximizing biomethane production and represent a significant advancement in valorizing wastes from pig farms and wineries, promoting a circular and sustainable economy.